AN EXTRACTION OF SOLITON SOLUTIONS OF THE NONLINEAR MATHEMATICAL MODEL IN A MAGNETO-ELASTIC CIRCULAR ROD - Agamalieva, Latifa; Alsindi, Ban Jamal Khalid; Bulut, Hasan; Orujova, Malahat (Jomard Publishing, 2026)
We establish novel computational soliton solutions for the M-truncated longitudinal wave equation in a magneto-electro-elastic (MEE) rod in form of exponential functions. We successfully put these solutions in hyperbolic functions form. The Kudryashov expansion method (KEM) is used to find different dynamic wave structures of soliton solutions within the context of evolutionary dynamic structures of solitary wave solutions. This method offers a proficient approach for executing soliton solutions. In order to illustrate a solution profile and features, we choose suitable parameters values. The empirical demonstration of the physical behavior of these solutions aims to enhance comprehension of the physical phenomena associated with the dynamical models employed in mathematical physics. © 2026, Jomard Publishing. All rights reserved.
Keywords: Kudryashov expansion method; longitudinal wave equations; M-truncated derivative; soliton solutions